2022
DOI: 10.1001/jamaoto.2022.1174
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation for Papillary Microcarcinoma of the Thyroid

Abstract: y 4. Carneiro-Pla DM, Solorzano CC, Irvin GL III. Consequences of targeted parathyroidectomy guided by localization studies without intraoperative parathyroid hormone monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…RFA can be used as an effective and safe method for the treatment of PTMC close to thyroid capsule and PTMC far from thyroid capsule, as shown in our study. RFA is a minimally invasive alternative with promising outcomes and preservation of thyroid parenchyma, which that reduces the need for post-treatment replacement thyroid hormone, as reported [16][17][18].…”
Section: Discussionmentioning
confidence: 93%
“…RFA can be used as an effective and safe method for the treatment of PTMC close to thyroid capsule and PTMC far from thyroid capsule, as shown in our study. RFA is a minimally invasive alternative with promising outcomes and preservation of thyroid parenchyma, which that reduces the need for post-treatment replacement thyroid hormone, as reported [16][17][18].…”
Section: Discussionmentioning
confidence: 93%
“…RFA has been rapidly promoted as the first approach for treating benign thyroid tumors or even for the palliative treatment of metastatic lymph nodes in patients with thyroid cancer because it is minimally invasive and has no impact on aesthetic appearance ( 27 ). Multiple studies have reported that using RFA for patients with PTMC was safe, effective, and reliable ( 28 , 29 ). Our study confirmed the safety, efficacy, and reliability of RFA in treating T1N0M0 PTC.…”
Section: Discussionmentioning
confidence: 99%
“…RFA is not recommended for treating these aggressive subtypes. The combined analysis of molecular markers—such as the BRAF , RAS , TERT promoter, RET , and TP53 genes, along with the fusion genes RET / PTC , PAX8/PPARG , and NTRK [ 61 - 63 ]—in conjunction with the application of artificial intelligence [ 64 ] may facilitate the accurate evaluation of the aggressiveness, prognostic implications, and recurrence risk of PTC.…”
Section: Future Directionsmentioning
confidence: 99%